Relationship between reasons for practicing and sportpersonship behaviors in young handball players - David Sánchez Oliva; Francisco Miguel Leo Marcos; Pedro Antonio Sánchez Miguel; Diana Amado Alonso; Tomás García Calvo (Federación Extremeña de Balonmano; University of Extremadura, 2010)
Abstract The main aim of this work was to analyze the relationships among Self-Determination Theory and sportsmanlike and antisocial behaviors in low categories. However, we recruited 127 handball players from alevine, infantile and cadet categories who filled several questionnaires to measure motivation in sport (SMS: Pelletier, Fortier, Vallerand, Tudson, Brière y Blais, 1995), satisfaction of the three psychological needs (EMM: García Calvo, Sánchez Miguel, Leo, Sánchez Oliva, y Gómez, 2010) and sportspersonship behaviors y (MSOS: Vallerand, Brière, Blanchard, y Provencher, 1997). Through the data analysis, we could demonstrate that greater self-determination levels were significantly associated with sportsmanlike conducts, as well as lower self-determination reasons were related with antisocial behaviors. Furthermore, we highlighted the autonomy as the strongest predictor of an adequate participation, whereas external regulation predicted negative critic. Finally, we emphasized the importance to promote self-determinated behaviors in young participants in the sport context, getting more adaptative conducts during the game.  Keywords: Self-determination, psychological mediators, sportsmanlike, handball.